Inovasi Madrasah: Strategi Pembelajaran Daring di Masa Pandemi - Hanum OK, Azizah (Islamic Education, 2021)
The influence of the Covid-19 pandemic, which robs people of their rights and movements in carrying out activities outside the home. Until now, economics, social, and even education have not found a common ground in direct learning, even some schools in the corners of the city are desperate to do face-to-face learning. Complaints of parents, students, and educators as one unit found the reason that continuous learning online at home is not effective. This paper tries to analyze how effective online learning was during a pandemic and how enthusiastic students were when learning online. The discussion of this article proves that society is starting to adapt to technological developments that focus on learning. Furthermore, madrasas make good progress through their teaching staff and educational staff. The discussion of this article proves that society is starting to adapt to technological developments that focus on learning. Furthermore, madrasas make good progress through their teaching staff and educational staff. Madrasah innovation followed by support from the community made the goal of distance learning an alternative in carrying out the teaching and learning process. The results of this study will also be used as a reference in developing and finding new theories related to the effectiveness of distance learning. The results of this study will also be used as a reference in developing and finding new theories related to the effectiveness of distance learning.